Optimalisasi Pelayanan Perpustakaan Sebagai Upaya Pemberdayaan Masyarakat Untuk Meningkatkan Literasi Anak Di Desa Pulau Terap, Kecamatan Kuok, Kabupaten Kampar, Provinsi Riau - Suyanto, Suyanto; Erliansyah, Mhd. Daffa; Wahyudi, M. Irfan; Fazikri, Heldi; Nurhayati, Naura; Rahmadani, Oki; Nasaf, Nabil Al; Aprialini, Muthia Hidayah; Salsabila, Aurenia; Hasanah, Layla Tillawatil; Putri, Dwita Puspa Oktaviani; Anisa, Syafira (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2025)
The low reading interest among children in Pulau Terap Village, Kuok District, Kampar Regency is caused by limited competence of library managers, minimal community participation, and lack of adequate programs and facilities. This activity aims to optimize Perpustakaan Cerdas Abadi services through community empowerment to improve children's literacy. Qualitative methods were used through observation, interviews with library managers, community leaders, parents, children, and activity documentation. Empowerment was conducted in stages including community awareness, manager capacity training, and literacy program implementation. Three innovative programs were implemented: